Relationships Between Tropical Ascent and High Cloud Fraction Changes With Warming Revealed by Perturbation Physics Experiments in CAM5 - Kathleen A. Schiro; Hui Su; Yuan Wang; Baird Langenbrunner; Jonathan H. Jiang; J. David Neelin (Geophysical Research Letters)
Abstract Tropical ascent area (Aa) and high cloud fraction (HCF) are projected to decrease with surface warming in most Coupled Model Intercomparison Project Phase 5 (CMIP5) models. Perturbing deep convective parameters in the Community Atmosphere Model (CAM5) results in a similar spread and correlation between HCF and Aa responses to interannual warming compared to the CMIP5 ensemble, with a narrower Aa corresponding to greater HCF reduction. Perturbing cloud physics parameters produces a comparatively smaller range of Aa responses to warming and a dissimilar HCF‐Aa relation to that in CMIP5; a narrower Aa corresponds to less HCF reduction, likely due to cloud radiative effects. A narrowing of Aa corresponds to a regime shift toward stronger precipitation in both experiments. We infer that model differences in deep convection parameterization likely play a greater role than differing cloud physics in determining the diverse responses of Aa and HCF to warming in CMIP5.